Age-Tailoring of Strategies in Workshops at EAFIT Children's University (2015)
Mystery, play, debate and creation are part of the tools that are implemented according to age groups. Age distribution, a strategy that promotes the processes of learning, teaching and social appropriation of scientific knowledge with children and young people.